2016
DOI: 10.18632/oncotarget.13256
|View full text |Cite
|
Sign up to set email alerts
|

Circulation autoantibody against Lamin A/C in patients with Sjögren's syndrome

Abstract: Lamin A/C proteins are major components of nuclear laminae and were encoded by the LMNA gene. Recent studies have found that in addition to provides nuclear-membrane strength; it also regulates the gene expression. Lamin A/C has been confirmed as an autoantigen in RA, SLE and vasculitis. Anti-Lamin A/C antibodies also have been found by indirect immunofluorescence method. In this study, we used various research methods to confirm Lamin A/C is an autoantigen in Han Chinese patients with confirmed Sjögren's synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Similarly, some nuclear proteins have been identified and described as autoantigen like hnRNP family (hnRNP A1 and hnRNP A2) [9]. In our previous study, HUVEC and HEK293 cells showed immunofluorescence and nuclear staining pattern of BD sera [5][6][7][8], which looks very similar to the target protein staining pattern [10][11][12].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, some nuclear proteins have been identified and described as autoantigen like hnRNP family (hnRNP A1 and hnRNP A2) [9]. In our previous study, HUVEC and HEK293 cells showed immunofluorescence and nuclear staining pattern of BD sera [5][6][7][8], which looks very similar to the target protein staining pattern [10][11][12].…”
Section: Introductionsupporting
confidence: 55%
“…The immunoprecipitation assay was performed as per our recently published study [12]. The C-NuMA was incubated at 4°C temperature for overnight, with equal volume of positive BD sera, which was used in the Western blotting.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…We next investigated the common features of the identified protein antigens of the tumor-specific dominant B cell clones. Knowledge-based exploration of the biological and clinical features of the protein antigens revealed that almost all the humoral protein antigens we discovered in tumor environments have also been reported as immunological targets of humoral autoimmunity in multiple autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), myasthenia gravis (MG), multiple sclerosis (MS), primary biliary cirrhosis (PBC), and Sjogren's syndrome (SS) [11][12][13][14][15][16][17][18][19][20][21][22] (Table 1). This shared feature of humoral immunity in tumors and autoimmunity in view of their target protein antigens suggested that these two clinically important aspects of immunological dysregulations are attributable to common molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%